2019
DOI: 10.3390/ani9080517
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Meat Characteristics of the First Awassi–Rambouillet Callipyge Backcross

Abstract: The Awassi breed is desirable due to its resilient traits, but shows poor lean meat content on the carcass; the callipyge mutation may enhance growth and meat characteristics. The first backcross of callipyge Awassi–Rambouillet (CRAW) lambs was generated by mating Awassi ewes with heterozygous F1 (50 % Awassi and 50 % Rambouillet) rams for the callipyge mutation. A fattening trial with carriers of CLPG (CRAW), non-carriers (RAW), and Awassi (AW) ram lambs was conducted for 94 days and growth and meat character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…At the end of the fattening period, all lambs were slaughtered for the evaluation of carcass traits and meat quality, as previously described [10,11,12]. Briefly, carcasses were divided into four parts, namely shoulder, rack, loin, and leg cuts, in addition to the fat tail and the rib-eye area, fat depth, tissue depth, rib fat depth, eye muscle width, eye muscle depth, eye muscle area, and leg fat depth, measured as previously described [10,12]. The right leg was dissected to determine muscle, bone, subcutaneous fat, and intermuscular fat components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the fattening period, all lambs were slaughtered for the evaluation of carcass traits and meat quality, as previously described [10,11,12]. Briefly, carcasses were divided into four parts, namely shoulder, rack, loin, and leg cuts, in addition to the fat tail and the rib-eye area, fat depth, tissue depth, rib fat depth, eye muscle width, eye muscle depth, eye muscle area, and leg fat depth, measured as previously described [10,12]. The right leg was dissected to determine muscle, bone, subcutaneous fat, and intermuscular fat components.…”
Section: Methodsmentioning
confidence: 99%
“…Longissimus muscles were excised from the right side of loin cuts, cleaned from all subcutaneous fat, vacuum-packaged, and frozen at −20 °C for meat quality measurements, as described [13]. Meat quality parameters were Warner–Bratzler shear force values for cooked meat samples, water holding capacity, cooking loss, and color coordinates (whiteness, redness, yellowness) [10,12,13].…”
Section: Methodsmentioning
confidence: 99%
“…The CLPG causes muscle hypertrophy that is restricted to the pelvic and lumbar muscles with little or no effect on the anterior skeletal muscles (Cockett et al, 1996). As described in several studies, this gene also provides a higher leg score and carcass percentage, larger longissimus loins, superior leanness composition, higher leg values, higher percentage of dressing percentages, and optimal feed conversion, as well as higher body weight and Baron-Crevat indices (Jackson et al, 1997;Jawasreh et al, 2019;Esen et al, 2022b).…”
Section: Introductionmentioning
confidence: 88%
“…In addition, Longissimus muscle area for Awassi, Tushin and Red Karaman fat tailed breeds was similar(Esenbuga et al, 2001). Meanwhile, Longissimus muscle area, width, and depth were found to differ among three different lamb genotypes(Jawasreh et al, 2019).…”
mentioning
confidence: 88%
“…Al. (2019) reported that all measurement of fat thickness were affected by lamb's genotype when comparing Awassi to Awassi crossbred lambs(Jawasreh et al, 2019). In addition, Longissimus muscle area for Awassi, Tushin and Red Karaman fat tailed breeds was similar(Esenbuga et al, 2001).…”
mentioning
confidence: 99%